Negosiasi Antara PSK (Pekerja Seks Komersial) Dengan Pelanggan (Tamu) Di Kota Bengkulu - Erwanda, Ega Silvia; Narti, Sri; Heriniazwi, Martha (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Commercial Sex Workers) in Bengkulu City and customers (guests) in maintaining relationships. This research method is descriptive qualitative. The technique for determining informants in this research used random sampling techniques. Data collection techniques used observation, interviews and documentation. Data analysis techniques use data reduction, data display (data presentation) and conclusion drawing/verification. Based on the research results, it was concluded that interpersonal communication patterns can be broken down into several stages, including the contact stage, involvement stage, familiarity stage, destruction stage and termination stage. These stages can describe the communication pattern between prostitutes in Bengkulu City. Interpersonal communication in prostitution transactions is considered effective because of several characteristics of interpersonal communication. The first thing that stands out is the openness between prostitutes and guests. Openness in online prostitution transactions is defined as clarity in providing information from both parties, where both parties agree to continue the negotiation process. Secondly, empathy is the ability to know what other people feel. This includes when prostitutes and customers understand each other. Third, positive feelings (positiveness), a positive attitude in interpersonal communication means that prostitutes and customers view themselves positively and respect other people, using polite language when communicating. Fourth, equality, in this case the desires between prostitutes and customers. which has one goal.